Personalentwicklung in der Notaufnahme - Wasser, Christoph; Riessen, Reimer (DMW - Deutsche Medizinische Wochenschrift, 2019)
In the last years, the number of patients in German emergency department (ED) is rising continously. At the same time, it is diffcult to find enough physicians to occupy the positions in the ED. Therefore human resources development is critical for the success of any ED. This article describes human resources development and recruitment in the context of current health policy trends in Germany.
Keywords: Notaufnahme; Personalentwicklung; Weiterbildung; Notfallmedizin; Arbeitszeitmodelle